Analysis of Reporting and Investigation Problems in Criminal Procedure - I Ketut Kasna Dedi; Gratia Clara Hadjon; Choirul Anam (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Laws in Indonesia, especially regarding criminal procedural law, are often unprofessional and overlapping or one-sided. The purposes of this paper are as to know the follow-up if there is a court request regarding a case but it is not processed legall, and to find out the follow-up to the problem if there is a case when the initial investigation is not enough. This research uses qualitative research. Based on the above discussion, it can be concluded that the case was in the reporting stage, the police did not follow up on the case report. In this case, the reporter can submit a pretrial application as a basis for the case not being processed for one year. The reporter must first confirm the letter on the progress of the investigation results. Then, regarding the issue of sufficient evidence investigation, the Court considers the minimum requirement of two pieces of evidence and examination of a potential suspect for transparency and protection of a person's human rights so that before a person is declared a suspect he can provide a balanced statement.